Political Branding via Social Media: Analyzing Computer Mediated Communication of 2024 Presidential and Vice Presidential Candidates on Instagram - Sandika Rhamadona; Panuju, Redi (Journal of International Multidisciplinary Research, 2024)
The digital era has significantly transformed lifestyles, particularly in Indonesia, where computer-mediated communication (CMC) now plays a prominent role in human interactions. In public spaces, individuals often prioritize their digital devices over engaging with those around them. The rise of the internet generation has integrated media and communication into essential elements of daily life. This study focuses on the analysis of hashtag trends related to general elections, such as #capres2024, #cawapres2024, and #pemilu2024, on Instagram, and their influence on user perceptions. It examines the role of hashtags in CMC practices on Instagram during electoral periods. Through the analysis of seven samples, the study reveals that while certain posts align with the electoral purposes of the hashtags, others use these hashtags for visibility without relevance to the elections. The research underscores Instagram’s potential for reshaping political branding and enhancing voter engagement. It demonstrates that the strategic application of hashtags, combined with high-quality visuals and interactive features, can amplify the visibility and impact of political messaging. By integrating CMC and political branding theories, this study presents a framework for understanding how digital tools can foster a more engaged and informed electorate.